A percepção dos executivos expatriados italianos sobre a gestào brasileira - Elis Regina de Paula (2005)
Correlated factors as the economic globalization, the opening of the markets and the increasing competition among companies have driven organizational researchers to looking for to understand the characteristics that provide successful answers to the new challenges ofthe market, especially, the ones derived from the external environment. Within this new scenery, the expatriate executive gains importance and prominence. This kind of executive leaves his home country to work temporarily in a foreign country. When he arrives at the host country, the cultural shock is hard and becomes one of the causes of the adaptation troubles. The expatriated executive usually has to re-learn to work, to accept the local culture of the host country and still to produce results that justify to the head office, his sending. This study sought to investigate how the Italian expatriated executives adapted themselves to theBrazilian culture, what are facilitative and inhibiting factors of their adaptation, and mainly how they perceive the Brazilian management practices. The research sample were composed by fifteen executives selected according to the above mentioned conditions, and who work atState of Minas Gerais and have been in Brazil for a period ranged from two to ten years. The collection of the data was accomplished through individual semi-structured interviews according to a previously elaborated agenda. The method of analysis used was the linguistic discourse analysis. First the semantic paths were figured out, including subjects and figures, beyond sub-groups that allowed to detail the level the analysis and strategies of persuasion: the construction of the discursive characters, the lexical choice, the silencing and the implicitand explicit relation. Under this methodological process two semantic paths were outlined: the one of cultural differences and the one of management practices. It was verified that the main difficulties of executives adaptation refer to Brazilians way to manage the issues ofpunctuality, informality, bias in the communication, language, lack of planning and difficulty of acceptance of the mistakes made by Brazilian workers. Related to the Brazilian managerial practices, the main criticism refers to the Brazilians fascination for foreign practices and theirindiscriminate adoption, especially, the American practices, and to the Brazilians jeitinho.